ANALISIS HORIZONTAL TAIL SIZING DENGAN PENDEKATAN EVALUASI KESTABILAN STATIK DAN DINAMIK LONGITUDINAL â STUDI KASUS PESAWAT TEMPUR IF-X C103 - Junitu Tikupasang, Dominicus
Horizontal tail of an aircraft is an important component of the aircraft in accomplishing its operation. Optimum horizontal tail design results in a good stability and control degree that meets the design requirement of the aircraft.